2001
DOI: 10.1016/s0038-0717(00)00153-x
|View full text |Cite
|
Sign up to set email alerts
|

Does soil acidity explain altitudinal sequences in collembolan communities?

Abstract: Altitudinal changes in collembolan communities were studied by sampling soil microarthropods along 3 a gradient from 950 to 2150m a.s.l., under a wide range of forest vegetation types. A multivariate 4 method showed that most changes in species composition followed changes in soil chemistry, humus 5 forms and vegetation. A transition from mull to mor humus, with concomitant soil acidification, was 6 observed with increasing elevation. It was observed that at a given elevation changes in soil acidity 7 occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
2
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 51 publications
7
60
2
4
Order By: Relevance
“…O CBM não é um componente isolado no solo; ao contrário, interage estreitamente com muitos componentes biológicos (Baretta et al, 2005), inclusive com níveis tróficos mais elevados, como as populações de colêmbolos (Hanlon, 1981;Sousa et al, 2004). A área NPF, ao contrário da área (Loranger et al, 2001). …”
Section: Análise De Componentes Principais (Acp)unclassified
See 1 more Smart Citation
“…O CBM não é um componente isolado no solo; ao contrário, interage estreitamente com muitos componentes biológicos (Baretta et al, 2005), inclusive com níveis tróficos mais elevados, como as populações de colêmbolos (Hanlon, 1981;Sousa et al, 2004). A área NPF, ao contrário da área (Loranger et al, 2001). …”
Section: Análise De Componentes Principais (Acp)unclassified
“…Maiores valores de qCO 2 revelaram maiores perdas de C na área NPF na forma de CO 2 por unidade de C microbiano (Baretta et al, 2005), enquanto as áreas NF, R e RF, ao contrário, apresentaram menores perdas de C. Assim, evidenciou-se que alterações nos atributos químicos e microbiológicos do solo causam modificações na abundância das famílias de colêmbolos, conforme discutido por vários autores (Loranger et al, 2001;Ponge et al, 2003;Sousa et al, 2004;Cutz-Pool et al, 2007).…”
Section: Análise De Componentes Principais (Acp)unclassified
“…The preference for acid, neutral or alkaline pHs by soil Collembola might explain the distribution of species over gradients of soil acidity (Hågvar and Abrahamsen, 1984;Chagnon et al, 2000;Loranger et al, 2001) and changes in the species composition of communities when subjected to anthropogenic acid or alkaline deposition (Hågvar and Kjøndal, 1981;Heungens and Van Daele, 1984;Kopeszki, 1992). It has been demonstrated that some Collembola, when allowed to chose between different chemical solutions, exhibited strong preferences according to pH, osmolarity and electrical conductance, and it was suggested that these preferences were indicative of ecological requirements of species or groups of species (Mertens, 1975;Hutson, 1978;Jaeger and Eisenbeis, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Maiores valores de qCO 2 indicam maiores perdas de C na área NPF na forma de CO 2 por unidade de C microbiano, enquanto as áreas NF, R e RF, ao contrário, apresentaram menores valores de qCO 2 e, portanto, são sistemas mais sustentáveis, com menores perdas de C. O valor do pH do solo tem sido reportado como atributo químico que modifica a comunidade de colêmbolos (LORANGER et al, 2001). Assim, evidenciou-se que alterações nos atributos químicos e microbiológicos do solo causam modificações na abundância das famílias de colêmbolos, conforme discutido por vários autores (LORANGER et al, 2001;PONGE et al, 2003;SOUSA et al, 2004;CUTZ-POOL et al, 2007).…”
Section: Análise De Componentes Principais (Acp)unclassified
“…Assim, evidenciou-se que alterações nos atributos químicos e microbiológicos do solo causam modificações na abundância das famílias de colêmbolos, conforme discutido por vários autores (LORANGER et al, 2001;PONGE et al, 2003;SOUSA et al, 2004;CUTZ-POOL et al, 2007).…”
Section: Análise De Componentes Principais (Acp)unclassified